El acto de ser en la distinción hombre y persona de Santo Tomás de Aquino - Formet, Eudaldo (Sapientia, 2015)
Saint Thomas obtained the distinction of man and person in the evidence of human evil, whose most important manifestations are the corporal and spiritual sufferings, which culminate in death, the weakness of the reason and the lack of harmony and order in his powers. For the suitable understanding of man, he places it in the scale of the entities according to the degrees of perfection. Therefore, it is deduced that man has only one being, though it is composed of body and spirit, which gives him life. It is the act of being of a spirit, which unifies all the human constitutives and provides a deeper individuality, than the one that other entities possess. Individuality or only incommunicability of man is expressed with the term «person», which has a logical, special and grammatical statute. The person expresses directly the being, without the mediation of the essence, and the transcendental ones, which explain his great perfection.